How do Obese Women Cope with Social Stigma? A Phenomenological Study - Farnaz Rahnavard; Ahmad Sadati; Masood Amini (Shiraz University of Medical Sciences, 2014)
Background: The findings of many studies confirm that obesity includes social stigma. Stigma involves several stereotypes that have negative psychosocial effects. The goal of this study was to evaluate the experience of social stigma in obese women with emphasis on their coping strategies.Methods: After the interview was done in the department with 24 Sleeve female candidate, their narratives were analyzed using descriptive phenomenological approach.Results: Results showed that obese women had undesirable experiences of social stigma. Nevertheless, they used coping strategies to adapt with new conditions. The main strategies revealed include social resistance; passivity; psychological problems and hysteria; extreme denial of self body image; social isolation; and ignorance of what others say (self empowerment).Conclusion: Social stigma of obesity affects the obese women negatively. Although obese women use several strategies to cope, with huge social and personal costs are imposed on them. To reduce these costs, policy-makers should pay attention to desensitization of obesity in society with emphasis on women. To this end, they can use media instruments on the one hand and make the cultural context and infrastructures such as school and universities on the other.